Analisis Kesulitan Belajar Mata Kuliah Geometri Analitik Bidang Pada Mahasiswa Program Studi Pendidikan Matematika UMS Tahun Akademik 2016/2017 - Subita, Riza Kurniawan, Muhammad Noor Kholid, M.Pd (2017)
This research aim is to analyze signs of difficulties and factors why students have difficulties in finishing part of geometry analytic. The approach used is descriptive qualitative research. The subject of this research is eight of the second semester students in Mathematics program study FKIP UMS. Collecting data method used includes documentation, questionnaire, and interview. The techniques used for analyzing data are data reduction, data presentation, and conclusion. The result of the research shows that students have difficulties, first the difficulties of output include the students' inability in remembering the analytic geometry formula. Both visual-spatial and sequential difficulties include student difficulties in sequencing the steps used to solve a problem or understanding the concept of analytic geometry. The factors that cause students have difficulties are first, internal factors include cognitive (creativity), affective (feeling), and psychomotor (intention). Second, external factors, such as the family environment, the community environment, and the university environment. The difficulties experienced by students can be used as a material consideration for lecturers, in preparing a semester lesson plan in order to obtain better mathematics learning result. Keyword: Difficulties, Students, Analytic Geometry.